Electrical resistance change in compact tension specimens of carbon fiber cement composites - Reza, F.; Yamamuro, J.A.; Batson, G.B.
The incorporation of a small volume of carbon fibers into a cement matrix can lead to multiple benefits including improvements in durability and tensile strength. In this paper, the smart material property of the composite which is its ability to respond to electrical stimuli was exploited. It was found that electrical resistance techniques which had previously been only applicable as investigative tools in fracture mechanics studies of metals could now be extended to the field of carbon fiber-reinforced concrete fracture mechanics. Compact-tension specimens of carbon fiber-reinforced mortar with volume percentages between
Keywords: ELECTRICAL PROPERTIES; PORTLAND CEMENT; COMPOSITE; FIBER REINFORCEMENT; IMPEDANCE